The miR-33a-5p/CROT axis mediates ovarian cancer cell behaviors and chemoresistance via the regulation of the TGF-β signal pathway - Li, Xin; Gao, Xuzhu; Yuan, Jia; Wang, Fancheng; Xu, Xiaolin; Wang, Chenglong; Liu, Huiqiang; Guan, Wencai; Zhang, Jihong; Xu, Guoxiong (Frontiers in Endocrinology, 2022)
Due to the lack of symptoms and detection biomarkers at the early stage, most patients with ovarian cancer (OC) are diagnosed at an advanced stage and often face chemoresistance and relapse. Hence, defining detection biomarkers and mechanisms of chemoresistance is imperative. A previous report of a cDNA microarray analysis shows a potential association of carnitine O-octanoyltransferase (CROT) with taxane resistance but the biological function of CROT in OC remains unknown. The current study explored the function and regulatory mechanism of CROT on cellular behavior and paclitaxel (PTX)-resistance in OC. We found that CROT was downregulated in OC tissues and PTX-resistant cells. Furthermore, CROT expression was negatively correlated with the prognosis of OC patients. Overexpression of CROT inhibited the OC cell proliferation, migration, invasion, and colony formation, arrested the cell cycle at the G2/M phase, and promoted cell apoptosis. In addition, miR-33a-5p bound directly to the 3’UTR of CROT to negatively regulate the expression of CROT and promoted OC cell growth. Finally, overexpression of CROT decreased the phosphorylation of Smad2, whereas knockdown of CROT increased the nuclear translocation of Smad2 and Smad4, two transducer proteins of TGF-β signaling, indicating that CROT is a tumor suppressor which mediates OC cell behaviors through the TGF-β signaling pathway. Thus, targeting the miR-33a-5p/CROT axis may have clinical potential for the treatment of patients with OC.